Takeki Kudoh’s Research on Modern Medical Science and Japanized Confucianism in Colonial Korea (Chosŏn) - Jae-Mok CH'OI; Jeŏng-Gon KIM (Uisahak, 2015)
This paper reviews Kudoh Takeki’s activity critically during the colonial Korea period, regarding his research on Medical Science and Japanized Confucianism. He managed ‘The Seoul Gynecological Hospital’for approximately 35 years in the Chosŏn period as a Japanese resident with Chosŏn status. He published medical knowledge about obstetrics through more than 280 articles, and attempted to improve the hygiene and health of ‘Korean Women’. He tried to complete his will toward ‘One Unity of Chosŏn and Japan’by terminating the Chosŏn culture ‘gene’as an intention. The purpose would enlighten Chosŏn by Japanese blessing. This paper aims to confirm his intention by two aspect of analysis by ‘Medical Science’as an occupation and ‘Confucianism’and the background of his thought. The content of Kudoh Takeki’s research in Chosŏn regarding Medical Science-Confucianism is described as below. First, the purpose and mission of Kudoh Takeki regarding Chosŏn was analyzed. The papers revealed the Kudoh Takeki mentioned only the ‘HusbandMurders of Corean Women’, which was defined by Kudoh Takeki as ‘A Special Crime of Corea’. This paper examined his intensions. Second, writings by Kudoh Takeki were listed to verify the ‘medical’field and ‘non-medical’field according to the subject. No list of contents was found for his more than 280 articles or essays in magazines/newspapers/publications, and these papers only described the Kudoh paper “A Special Crime of Corea”and studied the separate book publication by Kudoh THE GYNAECOLOGICAL RESEARCH OF HUSBANDMURDERS OF COREAN WOMEN, A SPECIAL CRIME OF COREA. Third, the genealogy of Confucianism of Kudoh Takeki was analyzed as his background of mental·thought by his hometown and the school he graduated from. The people from Kumamoto and Seiseiko school who were influenced by ‘Yi Toegye(李退溪)’of Chosŏn Confucianism were more active than general Japanese. Fourth, the practical activity of Kudoh Takeki in Chosŏn was described. The paper revealed that his brother Tadaske and Shigeo also stayed in Chosŏn to act as an important assistants for the Colonial Chosŏn Government-general. Kudoh was an important man in Japanese society in Chosŏn, acting as a member of 「Group of Same Origin」 and ‘Chosŏn Association of great Asia’which was an important organization assisting Colonial Chosŏn Government-general and was a representative position in Seoul district of Bukmichang-jeong(now Bukchang-dong) Fifth, Kudoh Takeki’s precise activity to terminate Chosŏn cultural ‘gene’and lead to enlightenment was analyzed by an examination of his Medical Science as an occupation and Confucianism as a background of his thought. Even he attempted to enlighten the brutal Chosŏn people in cultural aspects but it was only a tool to assist the colonial policy of Japan by emphasizing ‘Kyoikuchokugo(Imperial Rescript on Education)’to implant the Kodo-Seishin(Imperial Spirit). Analyzing the relationship of Kumamoto Practical Party with Yi Toegye, the intention of a deep connection toward ‘One Unity of Japan and Chosŏn’by colonial policy was revealed. In conclusion, the paper revealed the Japanese modernization frame to complete ‘One Unity of Japan and Chosŏn’and ‘Make people to obey the Japan Emperor’by enlightening the dark Chosŏn and merging them with Japan as Kudoh intended.